Analysis of Interfaith Marriage Registration in Indonesia: A Review of Regulations and Judicial Practices Post- Supreme Court Circular Letter Number 2 of 2023 - Nurdiani, Sari; Suartini, Suartini (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
Interfaith marriage has long been a reality in Indonesia's multicultural society. As experienced by celebrity couple Jamal Mirdad and Lydia Kandou, it has been a subject of debate among both the public and legal experts, illustrating the complexity of marriage laws in Indonesia. SEMA No.2/2023, was issued with the hope of ending the polemic, but it instead sparked controversy as it was considered inconsistent with the law, violating the principles of religious freedom and the constitutional rights of citizens and diversity. This research aims to understand the regulations regarding interfaith marriages in Indonesia and explore the court's practices in handling cases of interfaith marriages before and after the issuance of SEMA No.2/2023. A normative juridical research method is employed in this academic work, using two main approaches: the statute approach to examine relevant legal regulations and the analytical approach focused on data analysis and interpretation. The research findings indicate the need to harmonize and clarify the regulations governing the recording of interfaith marriages in Indonesia to put an end to the polemic. Although SEMA No.2/2023 was issued as a guide for judges in deciding on the recording of interfaith marriages, there are still court decisions approving applications for the recording of interfaith marriages after the issuance of SEMA.